2002
DOI: 10.4315/0362-028x-65.3.484
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella spp. Shedding by Alberta Beef Cattle and the Detection of Salmonella spp. in Ground Beef

Abstract: Breeder cows, cattle recently arrived at feedlots, and cattle about to be shipped for slaughter were tested for Salmonella spp. No Salmonella spp. were detected in fecal samples from breeding cows. Nineteen of 1,000 (1.9%) fecal samples from recently arrived feedlot cattle were positive for Salmonella spp. compared to only 2 of 1,000 (0.2%) fecal samples taken within 2 weeks of slaughter. The positive fecal samples were collected in 5 of 50 (10%) "recent arrival" pens tested and in 1 of 50 (2%) pens tested wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…According to the USDA National Animal Health Monitoring System, Salmonella Montevideo was one of the five serotypes most frequently shed by feedlot cattle (49), and Salmonella Anatum was one of the five serotypes most frequently shed by dairy cattle (48,50). Salmonella Enteritidis is usually associated with eggs and poultry and is uncommon in cattle (42).…”
Section: Enumerationsmentioning
confidence: 99%
“…According to the USDA National Animal Health Monitoring System, Salmonella Montevideo was one of the five serotypes most frequently shed by feedlot cattle (49), and Salmonella Anatum was one of the five serotypes most frequently shed by dairy cattle (48,50). Salmonella Enteritidis is usually associated with eggs and poultry and is uncommon in cattle (42).…”
Section: Enumerationsmentioning
confidence: 99%
“…Although no other serotypes were detected in pigeon and multiple environ-mental sample types, serotypes frequently implicated as the cause of disease were identified in the environmental samples. Salmonella Anatum and Salmonella Newport, which were isolated from the feed and manure samples respectively, are two of the most commonly detected serotypes in cattle (Smith and House, 1992;Sorenson et al, 2002). Salmonella Mbandaka, which was detected in a feed sample during the summer trapping period, is less frequently reported in cattle (CDC, 2004).…”
Section: Salmonellamentioning
confidence: 99%
“…For example, in 2005, the Salmonella serotypes accounting for 56% of human infections included Typhimurium (20%), Enteritidis (15%), Newport (10%), Javiana (7%), and Heidelberg (5%) (CDC, 2006). Another study found the predominant serotype to be S. typhimurium var Copenhagen (Sorensen et al, 2002). Other studies have reported the predominant serotype to be S. enteritidis (Domínguezet al, 2002;Mayrhofer et, 2004), S. bredeney (Duffy et al, 1999) and S. anatum (Mrema et al, 2006).…”
Section: Salmonella From Meatsmentioning
confidence: 97%